Coprescription of opioid and naloxone in office-based practice and emergency department settings in the United States. (March 2020) - Sohn, M.; Brinkman, R.; Wellman, G.S.
Abstract: Objectives: The objective of the study was to estimate the national rates of naloxone coprescribing with opioids in office-based practice and emergency department (ED) settings in the United States (US). Study design: This study is a cross-sectional study. Methods: We used the National Ambulatory Medical Care Survey (NAMCS) and the National Hospital Ambulatory Medical Care Survey (NHAMCS) datasets to estimate the national rates of naloxone coprescribing with opioids for the period 2014–2016. The analysis was stratified into office-based practice and ED settings. In ED settings, opioid and naloxone could be given to patients while they were in ED or as a prescription at discharge. Patients of all ages were considered for the analysis and sampling weights were applied to estimate national rates. Results: In office-based settings, 7918 sample visits included one or more opioid prescriptions (10.67 per 100 office visits). Of those, one included naloxone as a coprescription. In ED settings, the opioid prescription was given at discharge in 6124 sample visits (9.68 per 100 ED visits). Of those, two included naloxone as a coprescription. On the other hand, opioid was given to patients in the ED in 8811 sample visits (13.57 per 100 ED visits). Of those, 30 included naloxone as a coprescription. Conclusions: The rates of naloxone coprescribing with opioids were extremely low in office-based and ED settings in the US. Expanding access to naloxone is a key component of the public health response to the opioid crisis. Based on our study findings, promoting the coprescription of naloxone with opioids may provide greater access to naloxone for those who are at risk of opioid overdose. Highlights: Expanding access to naloxone is a key component of the public health response to the opioid crisis. The rates of naloxone coprescribing with opioids were extremely low in office-based and ED settings in the US. Promoting naloxone coprescribing may provide greater access to naloxone for those who are at risk of opioid overdose.